Genome engineering and gene drive in the mosquito aedes aegypti - St John, O; Oliver St John (2012)
Genetic control strategies are a novel method for reducing populations of pest insects such as the yellow fever mosquito Aedes aegypti, a major vector of several important arboviral diseases. This thesis describes efforts to develop new tools to engineer the Ae. aegypti genome and to better understand existing tools, and furthermore to use these to engineer a gene drive system in Ae. aegypti. The piggyBac transposon was found to be extremely stable in the germline of Ae. aegypti, and transposons engineered into the germline could not be remobilized with either an endogenous or exogenous source of piggyBac transposase. Conversely, somatic remobilization of piggyBac transposons was found to be readily detectable in the presence of a source of active transposase, the first report of such remobilization in Ae. aegypti. Toward new tools for genome engineering, the site-specific integrase from the phage φC31 was successfully used to promote exchange between a transgene cassette inserted into the genome of Ae. aegypti and a cassette in a plasmid vector, in the first demonstration of recombinase mediated cassette exchange technology in a pest insect species. The integrases from phages φRV1 and Bxb1 were not found to be active in the germline of the mosquito. Finally, development of a gene drive system in Ae. aegypti using an RNAi-mediated killer-rescue mechanism was attempted. Tissue-specific expression of tTAV-regulated-toxic effectors genes, using the promoter regions of the blood meal induced genes Carboxypeptidase A-1, 30Kb and Vitellogenin A, was possible, but sex-specificity was not achieved. A blood meal inducible lethal phenotype was not possible using the chosen promoters, with expression of the effectors either leading to death in early development or to a sublethal phenotype. RNAi against tTAV fused to the Mnp fragment of the dengue virus’ genome was tissue specific, but was found to be highly effective in the fat body suggesting that the Vitellogenin A was the best candidate for the engineering of killer-rescue systems in the mosquito.